2023
DOI: 10.1038/s41467-022-35709-0
|View full text |Cite
|
Sign up to set email alerts
|

A nitric-oxide driven chemotactic nanomotor for enhanced immunotherapy of glioblastoma

Abstract: The major challenges of immunotherapy for glioblastoma are that drugs cannot target tumor sites accurately and properly activate complex immune responses. Herein, we design and prepare a kind of chemotactic nanomotor loaded with brain endothelial cell targeting agent angiopep-2 and anti-tumor drug (Lonidamine modified with mitochondrial targeting agent triphenylphosphine, TLND). Reactive oxygen species and inducible nitric oxide synthase (ROS/iNOS), which are specifically highly expressed in glioblastoma micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 64 publications
(63 reference statements)
0
36
0
Order By: Relevance
“…Angiopep-2 (Ang) can specifically bind to the lipoprotein receptor-related protein 1 (LRP1) receptor, enhance the transport efficiency of NP across the BBB, and deliver drugs to the glioma. In addition, the overexpression of α4 or β1 integrin on the surface of macrophages can bind vascular cell adhesion molecule-1 (VCAM-1), promote the penetration of the BBB and target gliomas . To assess the ability of Ang-MMsaNPs to permeate the BBB, an in vitro model was established with Transwell inserts placed in 24-well plates.…”
Section: Resultsmentioning
confidence: 99%
“…Angiopep-2 (Ang) can specifically bind to the lipoprotein receptor-related protein 1 (LRP1) receptor, enhance the transport efficiency of NP across the BBB, and deliver drugs to the glioma. In addition, the overexpression of α4 or β1 integrin on the surface of macrophages can bind vascular cell adhesion molecule-1 (VCAM-1), promote the penetration of the BBB and target gliomas . To assess the ability of Ang-MMsaNPs to permeate the BBB, an in vitro model was established with Transwell inserts placed in 24-well plates.…”
Section: Resultsmentioning
confidence: 99%
“…The results depicted in Figure 4B,C demonstrate that the tumor volume was partially suppressed in the PDT ( 5) and PTT (6) treated groups compared to those of control groups (1)(2)(3)(4). This suggested that mPPy@COF-Por could partially eradicate tumor cells under single light irradiation.…”
Section: Anticancer Performance Of Mppy@cof-por Nanomotormentioning
confidence: 86%
“…Synthetic nanomotors, which can convert various energy sources into mechanical motion to achieve complex tasks in solution, have gained more and more attention [1,2] Compared with chemical and enzyme-powered nanomotors, [3,4] physical nanomotors driven by external fields, such as magnetic, ultrasound, light, and electric fields, offer more advantages for biomedical applications. For example, they are not limited by the availability of DOI: 10.1002/adhm.202301645 external chemical fuels (e.g., hydrogen peroxide (H 2 O 2 ), urea, or glucose).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wan et al constructed a nitric oxide (NO)-driven nanomotor (Ang-PAMSe), which could effectively penetrate the BBB for glioblastoma treatment. 135 Therefore, MNMs that can actively move and target drug delivery are hopeful to provide a new solution for crossing the BBB.…”
Section: Applications Of Light-driven Mnmsmentioning
confidence: 99%